3D visualization and morphometric analysis of spinal motion segments and vascular networks: A synchrotron radiation‐based micro‐CT study in mice. Issue 2 (7th October 2021) - Guo, Zhu; Li, Chengjun; Cao, Yong; Jiang, Liyuan; Zhang, Yi; Li, Ping; Zhou, Yongchun; Duan, Chunyue; Hu, Jianzhong; Lu, Hongbin
Abstract: The structure of spinal motion segments and spinal vasculature is complicated. Visualizing the three‐dimensional (3D) structure of the spine may provide guidance for spine surgery. However, conventional imaging techniques fail to simultaneously obtain 3D images of soft and hard tissues, and achieving such coimaging states of the spine and its vascular networks remains a challenge. Synchrotron radiation micro‐CT (SRμCT) provides a relatively effective and novel method of acquiring detailed 3D information. In this study, specimens of the thoracic spine were obtained from six mice. SRμCT was employed to acquire 3D images of the structure, and histologic staining was performed for comparisons with the SRμCT images. The whole spinal motion segments and the spinal vascular network were simultaneously explored at high resolution. The mean thickness of the cartilaginous end plates (CEPs) and the volume of the intervertebral discs (IVDs) were calculated. The surface of the CEPs and the facet joint cartilage (FJC) were presented as heat maps, which allowed for direct visualization of the thickness distribution. Regional division revealed heterogeneity among the ventral, central, and dorsal parts of the CEPs and between the superior and inferior parts of the facet processes. Moreover, the connections and spatial morphology of the spinal vascular network were visualized. Our study indicates that SRμCT imaging is an ideal method for high‐resolution visualization and 3D morphometric analysis of the whole spinal motion segments and spinal vascular network. Abstract : The visualization of 3D structure of spine helps guiding the spine surgery. Using SRμCT, the study observed the thoracic spinal segments and spinal vasculature simultaneously in a high resolution and demonstrated that SRμCT is an ideal way to obtain detailed 3D information of spinal structure.